Quality Changes of Orange Juice after DPCD Treatment - Liying Niu; Dajing Li; Chunquan Liu; Wuyang Huang; Xiaojun Liao (Journal of Food Quality)
Dense phase carbon dioxide (DPCD) offers advantages of enhanced physical and nutritional qualities during the processing of juices. Here, freshly squeezed orange juice was treated with DPCD, and changes of physical properties and volatile components were investigated and compared with the original untreated and thermally treated samples. The correlations among physiochemical properties were also examined based on Pearson correlation, cluster analysis (CA), and principal component analysis (PCA). Significant correlations were found among the particle size, color parameters, and volatile compounds in the DPCD-treated samples. The 12 parameters were clustered into three groups using CA and PCA, and the eight volatile compounds were separated within the three groups. Nonanal and citronellol were clustered in group I, and they increased for a longer duration of more than 40 min with higher levels than the control. Parameters in group II included D (4,3), L∗, a∗, ethyl butyrate, and trans-2-hexenol, and they linearly decreased after 10–60 min DPCD treatment. The parameters of b∗ and monoterpenes were clustered in group III, and they decreased within 40 min of DPCD treatment and then increased to an intermediate level. In addition, PCA clearly showed that the orange juice samples under DPCD for 10–60 min formed a “U” shape on the two-dimensional plot and that the samples treated by DPCD for 10 min and 20 min were closer to freshly squeezed orange juice than the heat-treated orange juice. This indicated that the nonthermal DPCD process offers the potential to be used more extensively in juice products.